Physico-Chemical Studies on Ber (Ziziphus mauritiana Lamk.) Germplasm under Sodic Soil Conditions of Lucknow - Ram, R.B.; Shukla, Ganesh; Dwivedi, Deepa H.; Kareem, Abdul (Indian Journal of Agroforestry, 2020)
Indian jujube or ber (Ziziphus mauritiana Lamk.) is grown in arid, semi arid and subtropical regions of India and contains a fair amount of vit-C and other nutrients. In a study initiated in Lucknow at Babasaheb Bhimrao Ambedkar University, physico-chemical characters of fruits of the 12 cultivars viz. Banarasi Karaka, Karali, Shootiess, Mehrun, Peundi, Gola, Jaffran, Chhuhara, Khinni, Desi, Kaithali and Illaichi were compared with four superior chance seedling trees of ber viz. Ambedkar: Ber 1, 2, 3, and 4. On the basis of evaluation, it was found that fruit length varied from 1.5-5.11 cm, width 1.51- 2.95 cm, fruit weight 2.44-21.82 g, volume 2.38-21.79 cc, specific gravity (0.93-2.01 g/cc), pulp % (2.20-21.21%), pulp/stone ratio 5.03-36.98, stone length 0.87-2.83 cm, stone width 0.42-0.92 cm, stone weight 0.12-1.08 g, T.S.S. 10.00-19.33%, acidity 0.01-0.43% and ascorbic acid 45.67-93.22 mg/100 g in different cultivars of ber. From the study cv. Mehrun was found to be the best in most of the parameters taken during the study. Superior chance seedling trees of ber had high vit-C content (70.78 to 93.22) although, fruit size was poor.